2016
DOI: 10.18632/oncotarget.7840
|View full text |Cite
|
Sign up to set email alerts
|

Insights from HuR biology point to potential improvement for second-line ovarian cancer therapy

Abstract: This retrospective study aimed to investigate the role that an RNA-binding protein, HuR, plays in the response of high-grade serous ovarian tumors to chemotherapeutics. We immunohistochemically stained sections of 31 surgically-debulked chemo-naïve ovarian tumors for HuR and scored the degree of HuR cytoplasmic staining. We found no correlation between HuR intracellular localization in tumor sections and progression free survival (PFS) of these patients, 29 of whom underwent second-line gemcitabine/platin comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…35 A study reported that RalA plays an important role in OC. 36 AHSG is also called as α-2 Heremans-Schmid glycoprotein, which could participate in signaling pathways associated with cancer. 37…”
Section: Discussionmentioning
confidence: 99%
“…35 A study reported that RalA plays an important role in OC. 36 AHSG is also called as α-2 Heremans-Schmid glycoprotein, which could participate in signaling pathways associated with cancer. 37…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased HuR expression and cytoplasmic localization in tumors correlate with poor disease prognosis and advanced tumor staging [ 12 , 48 51 ]. Thus, there are many data points from multiple laboratories over various tumor types that HuR is a strong candidate target in cancer [ 7 , 18 , 19 , 52 ]. In this study, MS444 is used here as a tool compound for proof-of-principle for pharmacological HuR inhibition, and that targeting HuR with MS-444 has anti-tumor activity as a monotherapy in multiple pre-clinical models for CRC.…”
Section: Discussionmentioning
confidence: 99%
“…HuR-transfected and control cells were fractionated, and immunoprecipitates of cytoplasmic lysates were prepared. HuR-bound mRNAs versus IgG-bound control were detected and quantified by qRT-PCR, as previously described (1,3,57,58), using the following specific probes from Thermo Fisher Scientific: STAT1 (Mm01257286_m1), B2M (Mm00437762_m1), REG3g (Mm00441127_m1), COX-2 (Mm03294838_g1), CFD (Mm01143935_g1), glyceraldehyde-3-phosphate dehydrogenase (GAPDH; Mm99999915_g1 and Hs02786624_g1), and HuR (ELAVL1; Mm00516011_m1 and Hs00171309_m1).…”
mentioning
confidence: 99%